2017
DOI: 10.1097/iio.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Ocular Surface Tumor Diagnostics

Abstract: Purpose To evaluate technologies and techniques available for the diagnosis of ocular surface tumors. Methods A review of the literature from 1947 to 2017, through the PubMed Database, was conducted in order to evaluate current diagnostic methods for ocular surface tumors. Results Ocular surface squamous neoplasia, conjunctival melanoma, and conjunctival lymphoma are the three most common ocular surface malignancies. Technologies available to assist with diagnosis of these conditions, in addition to full t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 66 publications
(86 reference statements)
2
86
0
Order By: Relevance
“…Conjunctival lymphoma classically presents as a chronic, sessile, pink-colored sub-epithelial conjunctival mass described as a “salmon patch” ( Fig. 1 ) [5, 27, 38]. Another presentation is that of a chronic follicular conjunctivitis ( Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Conjunctival lymphoma classically presents as a chronic, sessile, pink-colored sub-epithelial conjunctival mass described as a “salmon patch” ( Fig. 1 ) [5, 27, 38]. Another presentation is that of a chronic follicular conjunctivitis ( Fig.…”
Section: Reviewmentioning
confidence: 99%
“…The cases reported herein had clinical features highly suspicious for OSSN such as the absence of pigmentation in two patients (cases 1 and 3), mild pigmentation in two patients (cases 2 and 4), (12,13). However, currently, histopathology is superior in reporting tissue architecture at the macroscopic and microscopic level.…”
Section: Discussionmentioning
confidence: 89%
“…AS-OCT is a non-invasive imaging technique used in several fields of ophthalmology (15,16) . For conjunctival tumours, it is useful for directing diagnosis and management, as it provides high quality images of the internal structure and extension (12). Recent studies showed that low-pigmented CM is seen more frequently in eyes with light iris color and is associated with a higher rate of recurrences, distant metastases and death.…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is an acidophilic dye that has a selective affinity for nucleic acids and therefore has increased uptake by malignant cells, thereby causing staining. It has been shown to stain OSSN lesions with a sensitivity of 97% and specificity of 50% [ 44 , 50 ].…”
Section: Introductionmentioning
confidence: 99%